Imunolocalização de receptores de leptina no ovário de preás (Galea spixii Wagler, 1831) - Macêdo, Luã Barbalho de (Brasil, 2017)
Leptin, a cytokine produced by adipose cells, is the target of the scientific community for believing that it has an impact on the reproduction of the animals promoting puberty, folliculogenesis and oogenesis, estrous cycle and aiding in fertilization. The understanding of the mechanisms controlling the reproductive activity of Spix's Yellow-toothed Cavy (Galea spixii) plays a relevant role in the preservation of the species. Thus, the present work proposed to analyze the immunolocalization of leptin receptors (Ob-R) in the ovary of cavies. Ovaries from 20 adult, non-pregnant, healthy females were collected. The samples were fixed in 4% phosphate buffered paraformaldehyde, embedded in paraffin and sectioned for immunohistochemistry. The sections were photomicrographs and intensity of the reaction was measured. Strong immunoreaction was observed in oocyte and theca cells, moderate in ovarian stromal cells and large luteal cells and weak stained in granulosa, endothelial, perivascular and small luteal cells. When compared to receptor expression along follicular development it was observed that the oocyte and the theca cells remained with expression at the same intensity. However, the granulosa cells presented strong stained in the preantral stages, whereas in the antral follicles it presented low intensity. We conclude that in the ovaries of Galea spixii there is the presence of Ob-R in the main structures of the ovary sugesting that this hormone plays a fundamental role in the reproduction of this species
Immunolocalization of leptin receptor of Spix's Yellow-toothed Cavy (Galea spixii-Wagler, 1831) ovary
Keywords: Adipocitocinas; Folículos ovarianos; Corpo lúteo; Reprodução de roedores; Adipocytokines; Ovarian follicles; Corpus luteum; Rodent reproduction; CIENCIAS AGRARIAS::MEDICINA VETERINARIA